2010
DOI: 10.1007/s00432-010-0780-4
|View full text |Cite
|
Sign up to set email alerts
|

Focal adhesion kinase serves as a marker of cervical lymph node metastasis and is a potential therapeutic target in tongue cancer

Abstract: These results suggest that FAK may serve as a marker of cervical lymph node metastasis of tongue cancer and that RNAi targeting FAK could serve as a potential therapeutic for the treatment of tongue cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 30 publications
2
26
0
Order By: Relevance
“…Similarly, a study in 80 OSCC archival specimens showed that FAK expression was found in all tumors and 55 of them (69%) displayed a moderate to high expression. 7 A separate study also reported that FAK is expressed in 60 of 67 OSCC tumors (90%) and 38 of them (57%) exhibit a moderate to high expression. 23 Compared with the intensive studies in FAK expression in OSCC, relatively few researches examined the levels of pY397 in benign and malignant oral lesions.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Similarly, a study in 80 OSCC archival specimens showed that FAK expression was found in all tumors and 55 of them (69%) displayed a moderate to high expression. 7 A separate study also reported that FAK is expressed in 60 of 67 OSCC tumors (90%) and 38 of them (57%) exhibit a moderate to high expression. 23 Compared with the intensive studies in FAK expression in OSCC, relatively few researches examined the levels of pY397 in benign and malignant oral lesions.…”
Section: Discussionmentioning
confidence: 90%
“…5 In OSCC cells, the expression of FAK in the primary or invasive OSCC tumors is higher than that in benign oral tissues, and modulation of FAK expression or activity regulates the invasive properties of OSCC cells. [6][7][8] However, the role of Y397 phosphorylation (pY397) in the FAK-promoted invasiveness in OSCC cells and its possible mechanism is mostly unknown.…”
mentioning
confidence: 99%
“…As shown in Figure 4A and 4B, cells treated with 100 μM CoCl 2 significantly migrated faster (1.7 times in M139 cells and 1.2 times in M214 cells) than untreated cells in which their wounds had closed at 36 h for M139 and 16 h for M214 cells. A metastasis marker, pFAK (phosphorylated focal adhesion kinase (Jiang et al, 2010)) and LC3-II were determined in CCA cells treated with CoCl 2 using western blotting. As depicted in Figure 4C and 4D, the 100 μM CoCl 2 treated cells increased the levels of LC3-II and pFAK when compared with untreated cells.…”
Section: Cocl 2 Stabilized Hif-1α With Induction Of Autophagicresponsmentioning
confidence: 99%
“…FAK overexpression has been associated with breast cancer lung metastasis (37,38), and FAK inhibitors have been introduced in novel therapeutic strategies (20,(39)(40)(41). An association between FAK overexpression and lymphatic metastasis has been identified in non-small-cell lung, oral squamous cell, esophageal, gastric, tongue, laryngeal and endometrial cancer by retrospective analysis of clinical samples (42)(43)(44)(45)(46)(47)(48)(49). Upregulation of FAK in the SKOV-3/LN403 cell line and clinical pathological specimens suggests that it may contribute to the high lymphatic metastaticity of the SKOV-3/LN403 cell line.…”
Section: Discussionmentioning
confidence: 99%